Monks in motion: Buddhism and modernity across the South China Sea - Chia, Jack Meng-Tat (Oxford scholarship online, 2020)
Chinese Buddhists have never remained stationary. They have always been on the move. Why did Buddhist monks migrate from China to Southeast Asia? How did they participate in transregional Buddhist networks across the South China Sea? In Monks in Motion, Jack Meng-Tat Chia tells a story of monastic connectivity across the South China Sea during the twentieth century. Following in the footsteps of three prominent monks-Chuk Mor (1913-2002), Yen Pei (1917-1996), and Ashin Jinarakkhita (1923-2002)-Chia explores the connected history of Buddhist communities in China and maritime Southeast Asia.